Facilitating values awareness through the education of health professionals: Can web based decision making technology help?. (March 2016) - Godbold, Rosemary; Lees, Amanda
Abstract: Recent events in the health care landscape have focused nursing's collective mind on the role of values in health care delivery. For example, in England, the government has issued a mandate to health educators that places primacy on developing a workforce who prioritise and implement the core values of the National Health Service. In the current environment in which 'values' have become common currency, this paper begins by asking what values are, arguing for greater understanding and recognition of their intrinsic role in driving decisions. It then reports on research carried out in New Zealand exploring the potential of the Values Exchange web based educational technology to promote and facilitate a values aware health workforce. Qualitative thematic analysis from a cohort of pre-registration health professionals revealed new understandings about values through the facilitation of deeper, multi-layered thinking. The unique online space provided a safe pre-registration environment for deliberating complex cases, with students readily identifying advantages for future practice and patients. For lasting and meaningful change to occur, a fundamental shift is required in our understanding of values and how they ultimately impact on the way we individually and collectively deliver care to our patients. The Values Exchange may offer a contemporary and timely vehicle for achieving these goals.